Goodbye Saint Theresita's: A case study - Palangdao, Gracia (Animo Repository, 1979)
This case refers to a Pilipino teacher who got into trouble with her students due to her alleged unattainable demands. Her method in teaching the Pilipino subject did not allow the students to understand and cope up with the lesson. Her bad temperament is the obstacle to her good rapport with her students and other faculty members. Her frankness in using hurting words was destructive to the sensitive Benguet students. It is an administrative case because it challenges the principal, who is the administrator of the school to make a definite critical decision. Whether let a teacher stay or leave the school. In solution to the problem posed in this case, alternative actions were recommended by the writer in the latter part of the paper.